EGFR EXPRESSION IN RECTAL CANCER, RELATION TO THE FREAQUENCY OF LYMPH NODE METASTASIS - I. V. Stepanov; S. R. Altybaev; N. V. Krakhmal; К. V. Rachkovsky; D. A. Sorokin; S. G. Afanasyev; S. V. Vtorushin; М. V. Zavyalova (Сибирский онкологический журнал, 2017)
The processes of vital activity of cancer cells mainly depend on the production of growth factors and their receptors. The epidermal growth factor receptor (EGFR) is a member of the ErbB family of receptor tyrosine kinases. Normally, binding of EGFR ligands and transforming growth factor alpha (TGFα) induces receptor activation, which triggers erk and PI3K signaling pathways that control cell proliferation, migration, invasion and many other processes. A number of studies have shown that a high percentage of EGFR expression is observed in 25–82 % of cases with rectal cancer. Thus, the expression and mutation of the EGFR gene is associated with various variants of tumor progression and an unfavorable prognosis for malignant tumors of various localizations. The purpose of the study was to investigate the EGFR expression in cancer tissue and evaluate the relationship between EGFR expression and parameters of lymphogenous metastasis in patients with rectal cancer.  Material And Methods. Surgical specimens of 149 patients with stage T1–4N0–2M0, rectal adenocarcinoma, who were treated at the Cancer Research Institute of Tomsk National Research Medical Center, were studied using histological and immunohistochemical analyses. Positive EGFR expression was found in 88 (59.1 %) patients. Diagnosis was made according to WHO classification (2010). Results. When studying the EGFR expression in tumor cells on different depth of invasion, it was found that the positive expression of this marker was observed in cases with and without lymph node metastases. The analysis of the EGFR expression in various structures of the parenchymatous component of the tumor located in different layers of the intestinal wall showed that in the solid structures of the mucosa, the positive expression of EGFR was detected more often in cases without lymph node metastases. In patients with lymph node metastases, the percentage of the EGFR expression was lower.  A similar pattern was observed in discrete groups of tumor cells. Conclusion. The study showed the presence of heterogeneity of the expression characteristics of the epidermal growth factor in various tumor structures located at different depths of infestation. The relationship between the parameters of lymphogenous metastasis and the positive EGFR expression indicates the prognostic significance of this marker.